Uji Sifat Fisik dan Mekanik Pakan Ikan Buatan dengan Bahan Perekat Tepung Tapioka - Suprapto; Nurul Fathia; Sri Waluyo (Seminar Nasional Insinyur Profesional (SNIP), 2024)
The aims of this research were to determine the effect of addition tapioca flour on the physical and mechanical properties of fish feed (pellets) for tilapia fish aging of 12 weeks old with length 10 – 12 cm. The parameters observed were profile of pellet produced, fineness modulus of fish feed raw materials, moisture content, pellet hardness, water stability of pellet, terminal velocity, pellet density, bulk density of pellet, angle of repose and pellet color. The research was done at three variations of tapioca flour addition which were of 5%, 7.5% and 10% with 10000 g weight of samples for each treatments. The results show that the pellets produced have length of 7.5 - 8.0 mm, fineness modulus of fish feed raw materials ranging from 0.24 to 4.14, the particle size ranging from 0.11 to 1.88 mm, the moisture content of raw materials ranging from 4.24 to 8.46%, the water content of the pellets 10.21 - 12.31%, pellet hardness 5.43 - 9.63 N, water stability of pellets 6.31 - 93.7 minutes, terminal volicity of pellets 1,19 m/s – 0,0009 m/s, the density of pellets 0.71 g / cm3 - 0.81 g / cm3, bulk density of pellets 0,49 g/cm3 – 0,56 g/cm3, angle of repose 37,93o - 44,2o, and pellet color index: Ired 0.54 - 0.57, Igreen 0.35 - 0.36 and Iblue 0.07-0.09. Those are not much different with the commercial fish pellets. Fish pellets with tapioca flour adhesive of 10% in the composition have better water stability and hardness compared with the commercial fish pellets.